Synthesis, Characterization, and Antileishmanial Activity of Certain Quinoline-4-carboxylic Acids - Mazin A. S. Abdelwahid; Tilal Elsaman; Malik S. Mohamed; Sara A. Latif; Moawia M. Mukhtar; Magdi A. Mohamed (Journal of Chemistry)
Leishmaniasis is a fatal neglected parasitic disease caused by protozoa of the genus Leishmania and transmitted to humans by different species of phlebotomine sandflies. The disease incidence continues to increase due to lack of vaccines and prophylactic drugs. Drugs commonly used for the treatment are frequently toxic and highly expensive. The problem of these drugs is further complicated by the development of resistance. Thus, there is an urgent need to develop new antileishmanial drug candidates. The aim of this study was to synthesize certain quinoline-4-carboxylic acids, confirm their chemical structures, and evaluate their antileishmanial activity. Pfitzinger reaction was employed to synthesize fifteen quinoline-4-carboxylic acids (Q1-Q15) by reacting equimolar mixtures of isatin derivatives and appropriate α-methyl ketone. The products were purified, and their respective chemical structures were deduced using various spectral tools (IR, MS, 1H NMR, and 13C NMR). Then, they were investigated against L. donovani promastigote (clinical isolate) in different concentration levels (200 μg/mL to 1.56 μg/mL) against sodium stibogluconate and amphotericin B as positive controls. The IC50 for each compound was determined and manipulated statistically. Among these compounds, Q1 (2-methylquinoline-4-carboxylic acid) was found to be the most active in terms of IC50.